Marriage with the Intention of Divorce: A Comparative Study - Al-Laham, Mohammad Naif (Journal of Islamic and Religious Studies, 2022)
Marriage with the intention of divorce is contract in which all the terms and conditions of marriage are fulfilled but the husband intends, in his heart, to divorce the woman after a specific time, whether long or short. Most scholars deem this a valid marriage but the spread of this marriage amongst the expatriates for studying, tourism purposes or others resulted negative consequences. Few researchers and scholars deem it as ḥarām and invalid for many reasons. The study aims to find out which of the two opinions is correct, by considering the evidences of both the groups, weighing between them, and discussing them according to the comparative deductive analytical approach. The paper concludes that marriage with the intention of divorce is invalid, void, and null for many reasons, i.e; it is contrary to the main purpose of the marriage, which is permanence, it seems like temporary nikah, nikah mut’ah, nikah halalah, along with cheating and deceiving the woman and her guardian. Moreover, it contradicts manliness and leads to great corruptions and serious harm to the reputation of Islam and Muslims.